OPTIMIZATION OF TREATMENT TACTICS FOR CHILDREN WITH URINARY TRACT INFECTION (Western European Journal of Medicine and Medical Science, 2025)
Development of modern diagnostic methods and optimization of antibiotic therapy for urinary tract infection (UTI) in children. Determine the nature of the microbial landscape for a given region.